A quality status encoding scheme for PCB-based products in IoT-enabled remanufacturing - LI, Sijie; SHANG, You (Frontiers of Computer Science, 2021)
In this paper, a binary-extensible quality status encoding scheme, named IQSCT (IoT quality status code table), is proposed for the PCB-based product with available recovery options in remanufacturing. IQSCT is achieved by code evolution based on binary logic, in which the product flow and the quality information flow are integrated, and three key features of PCB-based product ( PCB-module association, assemblydisassembly logic, and disassembly risk) are involved in production costing.With IQSCT, the manufacturer can have better decisions to reduce remanufacturing cost and improve resource utilization, which is verified by a case study based on the real data from BOM cost and corresponding estimation of Apple iPhone 11 series.